Никола Тасић, Борислав Јовановић и Петар Поповић, Scordisci and the Native Population in the Middle Danube Region - Palavestra, Aleksandar (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Nikola Tasić, Borislav Jovanović, Petar Popović: Scordisci and the Native Population in the Middle Danube Region, ed. Nikola Tasić, Balkanološki institut SANU, Posebna izdanja knj. 48, Beograd, 1992.